Combination of Phytochemicals in the Management of Polycystic Ovarian Syndrome Induced in Rats - Temkar, Vimal; Menon, Sasikumar (Asian Journal of Biological and Life Sciences)
Background: Polycystic ovarian syndrome (PCOS) is a heterogeneous reproductive disorder and the most common endocrinopathy that leads to anovulatory infertility. PCOS is associated with wide spectrum of complications in various health aspects including anovulation, hyperandrogenism, hirsutism, infertility and menstrual disturbance. Metabolic dysfunctions like obesity, dyslipidemia, diabetes mellitus, cardiovascular risk and changes in psychological feature such as mood disorders and decreased quality of life are also associated with PCOS. Disruption in secretion rates and metabolism of androgens, estrogens and other reproductive hormones is the major characteristic of PCOS. Balancing the disrupted hormone levels is therefore an effective treatment strategy in managing PCOS. Materials and Methods : PCOS was induced in female Sprague Dawley rats with body weights between 180-200g by administrating oral doses of letrozole for 21 days. After PCOS induction, different combinations of mimosine, β-sitosterol and diosgenin along with clomiphene citrate were administered for 15 days. Body weight, food intake, water intake and cage side observations were recorded during the study. Serum testosterone, FSH, LH, estrogens and progesterone, oxidative enzymes and lipid profile were measured to determine the efficacy of treatments. Ovarian histopathological features were also examined by light microscopy. Results: Rats after letrozole induced PCOS showed significant aberrations in hormonal levels (p≤0.001, 0.01) compared with the normal control group indicating induction of PCOS. The treatment with combinations of phytochemicals was found to be effective in resolving and normalizing the disrupted levels of hormones and other biochemical parameters caused due to PCOS. Significant histological changes in ovarian histology after PCOS induction was found to have resolved among all treatment groups, indicating the ovarian recovery following therapy. Conclusion: Results indicate the effectiveness of treatment with a combination of bioactive phytochemicals for balancing reproductive hormone levels. The results suggest that abnormality in hormonal level and changes in ovarian histoarchitecture due to PCOS may be reversed with treatment regimen of administering bioactive phytochemicals as an adjunct with clomiphene citrate.
Keywords: PCOS; Bioactive phytochemicals; Clomiphene citrate; Mimosa pudica L.; β-sitosterol; Mimosine; Diosgenin.